Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1093/jhered/esr067
|View full text |Cite
|
Sign up to set email alerts
|

Inferred Paternity and Male Reproductive Success in a Killer Whale (Orcinus orca) Population

Abstract: We used data from 78 individuals at 26 microsatellite loci to infer parental and sibling relationships within a community of fish-eating ("resident") eastern North Pacific killer whales (Orcinus orca). Paternity analysis involving 15 mother/calf pairs and 8 potential fathers and whole-pedigree analysis of the entire sample produced consistent results. The variance in male reproductive success was greater than expected by chance and similar to that of other aquatic mammals. Although the number of confirmed pate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
72
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(80 citation statements)
references
References 73 publications
5
72
1
2
Order By: Relevance
“…Certainly, our results suggest that the genetic signature of a bottlenecks should be interpreted with caution when found in species known to have moderate to large variance in offspring number (as for example in the killer whale, [46]), or where large variance in offspring number is suspected (as for example in many marine species, [26]). In the killer whale example, large variance in offspring number was estimated based on parentage analysis and a demographic bottleneck was inferred from genetic data using the statistical approaches we examined in our study; the authors report that it is unclear whether a bottleneck actually occurred.…”
Section: Discussionmentioning
confidence: 99%
“…Certainly, our results suggest that the genetic signature of a bottlenecks should be interpreted with caution when found in species known to have moderate to large variance in offspring number (as for example in the killer whale, [46]), or where large variance in offspring number is suspected (as for example in many marine species, [26]). In the killer whale example, large variance in offspring number was estimated based on parentage analysis and a demographic bottleneck was inferred from genetic data using the statistical approaches we examined in our study; the authors report that it is unclear whether a bottleneck actually occurred.…”
Section: Discussionmentioning
confidence: 99%
“…DNA extraction and analyses were performed according to previously published methods [52]. Species was confirmed by fragment length of 16 s ribosomal DNA.…”
Section: Methodsmentioning
confidence: 99%
“…Barrett-Lennard (2000) showed that resident killer whale females in Northern resident population tend to choose mates with the most dissimilar dialect (though mating within pods have been observed in the Southern resident population, Ford et al, 2011b). If females choose males on the basis of acoustic divergence of a male's call with their own sounds, sexual selection towards faster call evolution would be expected.…”
Section: Temporal Stability and Change Of Call Repertoiresmentioning
confidence: 99%